Task shifting to clinical officer-led echocardiography screening for detecting rheumatic heart disease in Malawi, Africa. (19th December 2016) - Sims Sanyahumbi, Amy; Sable, Craig A.; Karlsten, Melissa; Hosseinipour, Mina C.; Kazembe, Peter N.; Minard, Charles G.; Penny, Daniel J.
Abstract: Background: Echocardiographic screening for rheumatic heart disease in asymptomatic children may result in early diagnosis and prevent progression. Physician-led screening is not feasible in Malawi. Task shifting to mid-level providers such as clinical officers may enable more widespread screening. Hypothesis: With short-course training, clinical officers can accurately screen for rheumatic heart disease using focussed echocardiography. Methods: A total of eight clinical officers completed three half-days of didactics and 2 days of hands-on echocardiography training. Clinical officers were evaluated by performing screening echocardiograms on 20 children with known rheumatic heart disease status. They indicated whether children should be referred for follow-up. Referral was indicated if mitral regurgitation measured more than 1.5 cm or there was any measurable aortic regurgitation. The κ statistic was calculated to measure referral agreement with a paediatric cardiologist. Sensitivity and specificity were estimated using a generalised linear mixed model, and were calculated on the basis of World Heart Federation diagnostic criteria. Results: The mean κ statistic comparing clinical officer referrals with the paediatric cardiologist was 0.72 (95% confidence interval: 0.62, 0.82). The κ value ranged from a minimum of 0.57 to a maximum of 0.90. For rheumatic heart disease diagnosis, sensitivity was 0.91 (95% confidence interval: 0.86, 0.95) and specificity was 0.65 (95% confidence interval: 0.57, 0.72). Conclusion: There was substantial agreement between clinical officers and paediatric cardiologists on whether to refer. Clinical officers had a high sensitivity in detecting rheumatic heart disease. With short-course training, clinical officer-led echo screening for rheumatic heart disease is a viable alternative to physician-led screening in resource-limited settings.